2017
DOI: 10.1080/09168451.2017.1385383
|View full text |Cite
|
Sign up to set email alerts
|

Titrated extract ofCentella asiaticaincreases hair inductive property through inhibition of STAT signaling pathway in three-dimensional spheroid cultured human dermal papilla cells

Abstract: Dermal papilla (DP) is a pivotal part of hair follicle, and the smaller size of the DP is related with the hair loss. In this study, we investigated the effect of titrated extract of Centella asiatica (TECA) on hair growth inductive property on 3D spheroid cultured human DP cells (HDP cells). Significantly increased effect of TECA on cell viability was only shown in 3D sphered HPD cells, not in 2D cultured HDP cells. Also, TECA treatment increased the sphere size of HDP cells. The luciferase activity of STAT r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…(Ling et al, 2017). Lastly, C. asiatica also demonstrated a positive activation effect on dermal papilla, improved the viability of dermal papilla cells and increased the expression of characteristic genes related to hair growth in the cells, thus providing good application prospects for baldness (Choi et al, 2017).…”
Section: Effects On Skin Diseasesmentioning
confidence: 94%
See 1 more Smart Citation
“…(Ling et al, 2017). Lastly, C. asiatica also demonstrated a positive activation effect on dermal papilla, improved the viability of dermal papilla cells and increased the expression of characteristic genes related to hair growth in the cells, thus providing good application prospects for baldness (Choi et al, 2017).…”
Section: Effects On Skin Diseasesmentioning
confidence: 94%
“…The C. asiatica extract and its triterpenoids had certain therapeutic and relieving effects on acne, baldness, vitiligo, atopic dermatitis, and wounds (Sawatdee et al, 2016;Choi et al, 2017;Ling et al, 2017;Ju Ho et al, 2018;Shen et al, 2019) (Table 4).…”
Section: Effects On Skin Diseasesmentioning
confidence: 99%
“…The research on herbs and active constituents as hair growth promoters has been driven by their less toxicity, easy availability, low‐cost, patient compliance and more than one mode of biochemical action . Specific effects of herbal extracts, polyherbal formulations, flavonoids and natural compounds on DPCs have been examined . In vivo hair growth promoting effects as proof of concept are also mentioned.…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…We observed that DPS-1 increased the viability and spheroid formation of 3D cultured HDP. Indeed, recent studies have shown that hair inductivity of HDP cells are markedly improved in 3D spheroid formation rather than 2D culture (Choi et al 2017). Therefore, promoting HDP inductivity by DPS-1 may contribute to establish protocol for HF generation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that WNT/β-catenin and TGFβ family interact to regulate the transcription of a number of genes, which is related with HF formation. Furthermore, there are synergistic effects between WNT/β-catenin and TGFβ signaling pathway in various cellular functions including tumorigenesis and stem cell differentiation (Choi et al 2017). Because TGFβ family is crucial for HF morphogenesis as well as hair cycle, we developed synthetic peptides which are structurally similar to endogenous human TGFβ family but possess unique sequences, which we named, dermal papilla stem cell activator-1 (DPS-1).…”
Section: Introductionmentioning
confidence: 99%